Mitochondrial Ion Channels in Cancer Transformation - Madamba, Stephen M.; Damri, Kevin N.; Dejean, Laurent M.; Peixoto, Pablo M. (Frontiers in Oncology, 2015)
Cancer transformation involves reprograming of mitochondrial function to avert cell death mechanisms, monopolize energy metabolism, accelerate mitotic proliferation, and promote metastasis. Mitochondrial ion channels are emerging as promising therapeutic targets mainly because of their connection to metabolic and apoptotic functions. This mini-review discusses how mitochondrial channels might be associated with cancer transformation; and expands on the possible involvement of the mitochondrial protein import complexes in such pathophysiological process.